Effects of interleukin-12 gene polymorphism on response to hepatitis B vaccination among hemodialysis Egyptian patients - Sawsan M Abdel-Moniem; Mohammed A Mohammed; Ziyad M Essam El-Deen; Hanan M Mostafa (SpringerOpen, 2019)
Background Hepatitis B virus (HBV) infection is a major health problem among hemodialysis (HD) patients. Interleukin (IL)-12 gene polymorphisms may be associated with immune response variability to recombinant HBV vaccines. The aim was to determine the correlation between IL-12 gene polymorphism and hepatitis B surface-antibody (HBs-Ab) titer in response to HBV vaccine among HD Egyptian patients. Patients and methods Seventy patients receiving long-term HD and 20 age-matched and sex-matched healthy controls were enrolled. All participants were non-HBV vaccinated and seronegative for HBV and HIV. Recombinant HBV vaccine was given (three-dose scheduled). Thereafter, HBs-Ab titer and IL-12 gene polymorphism were evaluated 8 weeks after the last vaccination dose. Results There was no response (HBs-Ab<10 μIU/ml) in 20% of HD patients and 10% of the controls. HBs-Ab titers showed no significant correlation with duration of HD, BMI, serum albumin, hemoglobin, leucocytic count, parathyroid hormone level, or IL-12 gene polymorphism. Responders to vaccination had significantly lower transferrin saturation and significantly higher levels of urea reduction ratio, Kt/V and lymphopenia. IL-12B genotype frequency was as follows: AA (58.3 vs. 55.6%), AC (37.5%) and CC (4.2 vs. 0%) in responders of either HD or control participants, respectively (P>0.05 for all). Conclusion There was no significant association between IL-12B gene polymorphism and HBs-Ab response in Egyptian HD patients. In HD patients, lymphocytopnea, diabetes mellitus (DM), high transferrin saturation and inefficient HD were associated with HBV vaccine hyporesponsiveness.